Setelah Kepergian Kartini - Harnawan, Tedy (Jurnal Sejarah, 2021)
The development of Kartini's figure was influenced by the Dutch thinking and their commitment to Colonial Ethical Policy since the early 20th century. Eleven years after her death, Abendanon's writing, â€œDoor Duisternis Tot Lichtâ€ (From Darkness to Light) in 1911 became a platform for Kartini's ideas that supported modern colonial education against the backward conditions of indigenous women in Java as a colony. Kartini became popular and instrumental among Europeans that built the women solidarity in the Netherlands and the Dutch East Indies. She became a national hero of Indonesian women, but she was also controversial because of her social intimacy with Dutch friends. Kartini was considered a part of colonial promotion. This paper focuses on the Dutch propaganda to portray and promote Kartini's characterization since 1904. Keywords: Kartini, Propaganda, Euforia, Colonial, Dutch